Pleiotrophin (PTN) is expressed in vascularized human atherosclerotic plaques: IFN-γ/JAK/STAT1 signaling is critical for the expression of PTN in macrophages - Li, Fuqiang (The Federation of American Societies for Experimental Biology, 2010)
Neovascularization is critical to destabilization of atheroma. We previously reported that the angiogenic growth factor pleiotrophin (PTN) coaxes monocytes to assume the phenotype of functional endothelial cells in vitro and in vivo. In this study we show that PTN expression is colocalized with capillaries of human atherosclerotic plaques. Among the various reagents that are critical to the pathogenesis of atherosclerosis, interferon (IFN)-γ was found to markedly induce PTN mRNA expression in a dose-dependent manner in macrophages. Mechanistic studies revealed that the Janus kinase inhibitors, WHI-P154 and ATA, efficiently blocked STAT1 phosphorylation in a concentration- and time-dependent manner. Notably, the level of phosphorylated STAT1 was found to correlate directly with the PTN mRNA levels. In addition, STAT1/STAT3/p44/42 signaling molecules were found to be phosphorylated by IFN-γ in macrophages, and they were translocated into the nucleus. Further, PTN promoter analysis showed that a gamma-activated sequence (GAS) located at −2086 to −2078 bp is essential for IFN-γ-regulated promoter activity. Moreover, electrophoretic mobility shift, supershift, and chromatin immunoprecipitation analyses revealed that both STAT1 and STAT3 bind to the GAS at the chromatin level in the IFN-γ stimulated cells. Finally, to test whether the combined effect of STAT1/STAT3/p44/42 signaling is required for the expression of PTN in macrophages, gene knockdowns of these transcription factors were performed using siRNA. Cells lacking STAT1, but not STAT3 or p42, have markedly reduced PTN mRNA levels. These data suggest that PTN expression in the human plaques may be in part regulated by IFN-γ and that PTN is involved in the adaptive immunity.—Li, F., Tian, F., Wang, L., Williamson, I. K., Sharifi, B. G., Shah, P. K. Pleiotrophin (PTN) is expressed in vascularized human atherosclerotic plaques: IFN-γ/JAK/STAT1 signaling is critical for the expression of PTN in macrophages